In vitro cytotoxic and antioxidant properties of the aqueous, chloroform and methanol extracts of Dicranopteris linearis leaves - Zakaria, Zainul Amiruddin; Mohamed, A. M.; Mohd Jamil, N. S.; Rofiee, Mohd Salleh; Abdullah, Muhammad Nazrul Hakim; Ahmad, Zuraini; Abdul Kadir, Arifah; Sulaiman, Mohd Roslan (Academic Journals, 2011)
The in vitro cytotoxic and antioxidant properties of the aqueous, chloroform and methanol extracts of the Dicranopteris linearis leaves were investigated in the present study. The cytotoxic effect was determined against the normal (3T3) and cancer cells’ lines (MCF-7, HeLa, HT-29, HL-60, K-562 and MDA-MB-231) using the 3,(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay, while the antioxidant activity was assessed using the DPPH radical and superoxide scavenging assays. Based on the results obtained, the aqueous extract was not effective against any of the types of cancer cells studied; the chloroform extract was effective only against MCF-7 and HeLa; and the methanol extract was effective against all the cancer cells used. Interestingly, all extracts failed to produce cytotoxic effect against the 3T3 cells (normal cell) indicating their safety. All extracts (20, 100 and 500 mg/ml) were found to exert antioxidant activity when tested using the DPPH radical and superoxide scavenging assays; with the methanol, followed by the aqueous and chloroform extracts exhibiting the highest antioxidant activity in both assays. The total phenolic content for the aqueous, methanol and chloroform extracts were 3112.1 ± 6.7, 3417.3 ± 4.7 and 1012.7 ± 5.3 mg/100 g gallic acid, respectively. In conclusion, the leaves of D. linearis possess potential cytotoxic activity against various types of cancer cell lines depending on the types of extracts used and antioxidant activity, which need to be further explored.